Histological Inflammation in Human Ureter either Healthy or Fitted with Double-Pigtail Stent or a Thin 0.3 F Suture Thread: A Preliminary Study - Benoît Vogt; Ilham Chokri (Advances in Urology)
Background. Ureteral stent intolerance reduces patients’ quality of life. It has been suggested that changes in the shape of stents could decrease discomfort. In previous studies, the innovative pigtail-suture stent (i.e., JFil® or MiniJFil®) with a thin 0.3 F suture thread significantly decreased stent-related symptoms. Fortuitously, a dilation of the ureter containing the sutures was discovered. In addition, no inflammation was seen on the ureter wall around the suture in endoscopy. In this preliminary study, we assessed ureteral inflammation in the human ureter when it was healthy or when fitted with a double-pigtail stent or a thread. Materials and Methods. After consent and inclusion of patients in the protocol, fifteen segments of ureters were collected during cystectomy procedures for bladder tumors. Ureteral inflammation was assessed on the histological section stained with hematoxylin-eosin. Histological grading (cumulative range of 0 to 6) assessing inflammation was performed on the ureter section for mucosa inflammation and inflammation in the muscle layer. Results. A marked ureteral inflammatory reaction was observed in all cases of ureters fitted with a double-pigtail stent with a mean inflammation score of 4.8 ± 0.4. The ureter fitted with the thin suture thread showed inflammation in only one case with a mean inflammation score of 1.8 ± 1.3 p=0.001. Conclusion. Although the study was limited by the small number of patients, it confirmed that the double-pigtail stent induced ureteral inflammation in all cases and the thin 0.3 F suture thread caused less ureteral inflammation than the double-pigtail stent. The concept of material reduction within the urinary tract seems necessary in order to decrease mucosal irritation. The JFil® or the MiniJFil® thread could meet this requirement.